2018
DOI: 10.1042/bsr20181033
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential value of miR-148b-3p, miR-151b and miR-27b-3p as biomarkers in acute ischemic stroke

Abstract: Cerebrovascular disease is the main cause of death in the world. Here, we explored whether circulating serum miR-148b-3p, miR-151b and miR-27b-3p could be as potential diagnostic biomarkers for diagnosing acute ischemic stroke. Seventy-seven IS patients and forty-two healthy controls matched for age and sex were enrolled in the present study. Blood samples were drawn from IS patients within the 24 h. The correlation analysis was performed by Spearman. The ability to distinguish patients from healthy controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 17 publications
(17 reference statements)
3
25
0
1
Order By: Relevance
“…The in vitro OGD/R SH-SY5Y model showed IGFBP3 was significantly decreased, which was opposite with miR-19a-3p expression. In agreement with our findings, decreased IGFBP3 expression was negatively correlated with miR-27-3p level in blood samples drawn from ischemic stroke patients [36]. Moreover, lower plasma concentration of IGF-1/IGFBP3 increased the risk of prevalent and incident dementia [37].…”
Section: Discussionsupporting
confidence: 91%
“…The in vitro OGD/R SH-SY5Y model showed IGFBP3 was significantly decreased, which was opposite with miR-19a-3p expression. In agreement with our findings, decreased IGFBP3 expression was negatively correlated with miR-27-3p level in blood samples drawn from ischemic stroke patients [36]. Moreover, lower plasma concentration of IGF-1/IGFBP3 increased the risk of prevalent and incident dementia [37].…”
Section: Discussionsupporting
confidence: 91%
“…A number of reports have previously demonstrated that circulating serum miRNAs may serve as potential non-invasive biomarkers for patients with AIS (5,29). For instance, Wang et al (29) reported that serum miR-497 expression was significantly enhanced in patients with AIS compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wang et al (29) reported that serum miR-497 expression was significantly enhanced in patients with AIS compared with healthy controls. Cheng et al (5) suggested that miR-148b-3p, miR-151b and miR-27b-3p may serve as potential biomarkers for diagnosing AIS, with the specific combination of miR-148b-3p and miR-27b-3p being more effective. In accordance with these previous observations, the levels of serum miR-135 in patients with AIS were analyzed based on etiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations